Specifics of the Financial Behaviour of Russians under the Influence of External Shocks in Recent Years - Tikhonova, Natalia (Journal of Economic Sociology, 2025)
The article describes the specifics of savings, credit, and debt behavior among representatives of the mass strata of the country’s population, as well as the dynamics of these changes from 2003 to 2023. It shows that this behavior is an important indicator reflecting not only the dynamics of Russians’ material wellbeing and their expectations for the future but also their perception of current events. New trends in the financial behavior of the mass strata, formed under the influence of recent external shocks, are revealed, including an increase in savings activity due to growing uncertainty about the future and a decrease in the share of individuals burdened by credit and debt, despite an increase in the volume of this burden among those who are tolerant of it. Additionally, it is shown that several provisions of classical concepts regarding the financial behavior of the population “work” in Russia with certain peculiarities. For example, while income levels affect the amount saved, they have little influence on saving activity itself. Savings, including substantial savings, are most common among older age groups (65+), rather than those nearing retirement age. Furthermore, savings are primarily accumulated not for specific expenditures but “for a rainy day.” Regarding factors influencing financial behavior, a decisive role among macro-level factors is played by feelings of uncertainty about personal and national futures. Consequently, even during periods of low income, in the presence of this uncertainty, individuals prefer to preserve their savings and reduce credit burdens. At the micro level, key determinants of savings behavior include planning horizons, subjective feelings of social and economic well-being, and approaching retirement age. In terms of credit and debt behavior, planning horizon is less significant, with general tolerance for debt coming to the fore.